2020
DOI: 10.2147/cmar.s244901
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of Radiation-Induced Secondary Malignancy Risk Between Sequential and Simultaneous Integrated Boost for the Treatment of Nasopharyngeal Carcinoma: Intensity-Modulated Radiotherapy versus Volumetric-Modulated Arc Therapy</p>

Abstract: This study aimed to compare the secondary cancer risk (SCR) between the sequential boost (SEQ) technique and simultaneous integrated boost (SIB) technique in intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) in patients with nasopharyngeal carcinoma (NPC) using the concepts of organ equivalent dose (OED) and excess absolute risk (EAR). Patients and Methods: IMRT-SEQ, VMAT-SEQ, IMRT-SIB, and VMAT-SIB plans were created with identical objective functions for five patients with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The nomogram was established based on the risk factors of age, race, AJCC, and chemotherapy. Important factors of radiation therapy technique, radiation dose and its distribution were not included due to the limitation of SEER database [19][20][21]. Thus, the nomogram could not provide well-discriminating ability.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram was established based on the risk factors of age, race, AJCC, and chemotherapy. Important factors of radiation therapy technique, radiation dose and its distribution were not included due to the limitation of SEER database [19][20][21]. Thus, the nomogram could not provide well-discriminating ability.…”
Section: Discussionmentioning
confidence: 99%
“…Following the discovery of X-rays, it was found that frequent exposure experienced by physicians increased their risk of developing cancer (13)(14)(15)(16)(17)(18). Studies on atomic bomb survivors (19)(20)(21)(22)(23)(24) and patients with cancer receiving radiation therapy (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) have found that the risk of tumorigenesis is associated with acute or fractionated high-dose radiation exposure. although opinions differ as regards the harm of low-dose radiation to the human body, the impact of low-dose radiation on cancer risk has gained scientific attention.…”
Section: Introductionmentioning
confidence: 99%
“…Researches regarding SCR have been reported that SCR increases as the volume of organs receiving radiation increases and as the distance from the source reduces [ 11 , 15 ]. In Hall et al’s studies, it was reported that SCR is approximately 1.0–1.8% higher (10 years survival rate) in IMRT than CRT [ 13 , 16 ]. It is also reported that secondary scattered doses at locations approximately at 20–50 cm from the iso-center were approximately 1.0–5.0 mGy per 1 Gy for planning target volume (PTV) in IMRT [ 17 ].…”
Section: Introductionmentioning
confidence: 99%